FAKTOR FAKTOR YANG MEMPENGARUHI PERMINTAAN MOBIL TOYOTA AVANZA DI KOTA SEMARANG - Mardani, Reza; SBM, Nugroho (Diponegoro Journal of Economics, 2013)
Demand of Toyota Avanza in Semarang city for year to year always even significant raising .This study aim to examine is influence between price of Toyota Avanza, income by consumer, post traded services, price of another car and expectations about level of price in the future for demand of Toyota Avanza using primer data. Methods to get data was quesioner tecnics with claster sampling methods had given to consumer of Toyota Avanza every Toyota Avanza dealers in Semarang city.             This research use Ordinary Least Square (OLS) estimation methods with three dummy variabel. Before all, was did classic assumptions test that is  heterokedasticity test and multikolinieritas test.            A significant positive relationship was observed between income by consumer and demand of Toyota Avanza, these influence had elastic. Other even, Significant negative relationship was observed between price of Toyota Avanza and demand of Toyota Avanza, these influense had elastic. So that, inclusion about Toyota Avanza still a superior goods to consumer of Toyota Avanza in Semarang city.Post traded services, price of other car and expextations aboout level of price in the future not influence for demand of Toyota Avanza.